Times of Terror - Jarvis, Lee. author. aut Link
IX, 201 p.
Keywords: Since 11 September 2001, the War on Terror has dominated global political life. The book takes a critical look at different ways in which the George W. Bush administration created and justified this far-reaching conflict through their use of language and other discursive practices.